The promise and challenges of gender data - Buvinic, Mayra; Carey, Eleanor (International Food Policy Research Institute, 2019)
Good data form the backbone of effective policy. While much progress has been made since 1975, the epigraph at the beginning of this chapter still, unfortunately, describes accurately the state of gender data in Africa south of the Sahara (SSA). Women and girls in these largely rural economies are widely acknowledged to be among those suffering the worst life outcomes and are among the groups most poorly represented in the data. The content of their days do not fit neatly into categories but straddle and blur the boundaries between “productive” and “nonproductive,” “public” and “private,” and “home” and “work,” challenging the conceptual frameworks for measurement that have largely been devised to capture the roles that men have traditionally played in more advanced economies. In some cases, this has led to poor measurement, and in others, no measurement at all. In recent years, however, the measurement community has begun undertaking methodological work to produce more accurate and policy-relevant information aimed at improving the lives of marginalized women and girls.